Short-term exposure of PM2.5 and PM10 increases the number of outpatients with eczema in Guangzhou: A time-series study - Zhang, Ji; Yang, Yicheng; Fu, Lin; Jing, Dian; Sun, Bo; Chen, Yilin; Chen, Junyi; Shen, Shuqun (Frontiers in Public Health, 2023)
Background: The worldwide prevalence of eczema has continued to rise over the past decades. This has led to emphasis on the association between air pollution and eczema. This study investigated the relationship between daily exposure to air pollution and the number of eczema outpatient visits in Guangzhou with the overarching goal of providing novel insights on the interventions for eczema aggravation and prevention. Methods: Daily air pollution data, meteorological data, and number of eczema outpatients were obtained from 18th January 2013 to 31st December 2018 in Guangzhou. A generalized additive model with Poisson distribution was used to assess the association between the number of eczema outpatient visits and short-term exposure of PM2.5 and PM10. In addition, the association of PM2.5 and PM10 by age (<65 years, ≥65 years) and gender was evaluated. Results: A total of 293,343 eczema outpatient visits were recorded. The obtained results indicated that a 10μg/m3 increase of the same day/ lag 1 day/ lag 2 days PM2.5 was associated with increments of 2.33%, 1.81%, and 0.95% in eczema outpatient risk, respectively. On the other hand, a 10μg/m3 increase of PM10 was associated with eczema outpatients risk increments of 1.97%, 1.65%, and 0.98% respectively. Furthermore, the associations of PM on the increment of eczema were similar in the male and female groups. Results obtained after age stratified analyses indicated that the strongest positive association between PM2.5 exposure and eczema were observed at lag 0 day with the percent changes being 4.72% and 3.34% in <12 years old, ≥12 and <65years old, and ≥65 years old groups, respectively. Conclusion: Short-term exposure of PM2.5 and PM10 increases the number of eczema outpatients especially among children and the elderly. The relationship between climate change and hospital resource arrangement should be payed attention by hospital managers which may aid in disease prevention and lower the health burden.